A Mode Solution for the Finite Deflections of a Circular Plate Loaded Impulsively - Guedes Soares, C. (Engineering Transactions, 1981)
The mode approximation technique as originally presented by MARTIN and SYMONDS [7] is applicable to rigid-plastic structures undergoing infinitesimal deflections. The extension of the mode approach to the finite-deflection range can be done by considering a series of instantaneous modes [5-7], or by assuming a permanent mode shape [9, 16]. The method proposed in [9] is further developed here and applied to the study of a circular plate loaded impulsively. The final deflection is obtained using a method developed by Jones for beams and non-axisymmetric plates [10]. Comparison with experiments and other theoretical treatments show good correlation.